Simvastatin impairs fracture healing under ischemic conditions - Schreiber, S.; Stutz, J.; Finkler, J.; Metzger, W.; Fritz, T.; Osche, D.; Hawi, H.; Razaeian, S.; Örgel, M.; Menger, M. D.; Pohlemann, T.; Liodakis, E.; et al. (Frontiers in Pharmacology, 2025)
Patients suffering from fractures are often required to take simvastatin during the bone healing phase due to co-morbidities. However, the impact of simvastatin on fracture healing under ischemic conditions remains unclear so far. Therefore, we analyzed in this study the effect of simvastatin on fracture healing in an established murine ischemia model. Mild ischemia of the right hind limb and a femoral fracture was induced in CD-1 mice. After stabilization of the fracture by an intramedullary screw, the animals received either 30 mg/kg body weight simvastatin per os daily or an equivalent amount of vehicle (control). Bone healing was analyzed by biomechanical as well as radiological, histomorphometric and Western blot analyses 2 and 5 weeks postoperatively. The fractured femurs of both groups exhibited a delayed healing throughout the study period. Bone formation, as assessed by micro-computed tomography, was significantly reduced in the callus tissue of femurs in simvastatin-treated animals compared to controls. Moreover, these femurs showed histomorphometric signs of ongoing healing and a tendency towards less bone tissue at 2 weeks after surgery. Western blot analyses revealed an increased expression of CD31 and phosphoinositide-3-kinase (PI3K) after simvastatin treatment, whereas the expression of bone morphogenetic protein (BMP)-2 was significantly decreased. In conclusion, these results demonstrate that simvastatin impairs fracture healing under challenging ischemic conditions. This effect is most likely caused by an imbalance of angiogenesis and osteogenesis in the callus tissue. These findings indicate that the use of simvastatin during fracture healing under ischemic conditions warrants careful reconsideration in clinical practice.